Engaging students in a critical style of reflective practice through formative assessment - Mohamad Azhari, Abu Bakar; Kartini, Abd Ghani; Ida Juliana, Hutasuhut; Jamayah, Saili; Norehan, Zulkiply; Nor Hasniah, Ibrahim (2022)
Higher education teaching and learning employ different approaches and techniques to empower students' learning experiences. The critical style of reflective practice in higher education is significant in preparing students for professional development, research competencies and deep learning (Glass, 2015). The word reflection has diverse meanings, described as the continuous and active engagement towards any form of knowledge resources with the employment of critical thinking (Dewey, 1983). Schön (1983) emphasised reflection activity as a method of re-evaluating experiences in different forms comprising individual comprehension of self and others. The critical style of reflective practice requires continuous efforts, attempts, and complex thought processing of unstructured ideas from various resources (Moon, 1999). Reflection also includes experiences and the development of insights, which enable the active functioning of cognitive and affective elements (Boud et al.,1985). Therefore, the growth of reflective practice needs active engagement and thinking to arouse individual performance in reflection (Boud, Keogh & Walker, 1996).